2014
DOI: 10.1002/ange.201311124
|View full text |Cite
|
Sign up to set email alerts
|

Photoswitching CO2 Capture and Release in a Photochromic Diarylethene Metal–Organic Framework

Abstract: We demonstrate herein a promising pathway towards low-energy CO 2 capture and release triggered by UV and visible light. A photosensitive diarylethene ligand was used to construct a photochromic diarylethene metal-organic framework (DMOF). A local photochromic reaction originating from the framework movement induced by the photoswitchable diarylethene unit resulted in record CO 2 -desorption capacity of 75 % under static irradiation and 76 % under dynamic irradiation.Diarylethene derivatives are one of the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…Thed iarylethene MOF (1)w as synthesized by using the previously reported method. [23] Ther esulted crystals determined at 293 Ki sc onsistent with the reported value and shown in Figure 1. As UV light cannot penetrate into the crystal samples,t hereby the samples used in this work are treated by ball milling.T he resulted bulk samples are confirmed by powder X-ray diffraction (Supporting Information, Figure S1), SEM (Supporting Information, Figure S2a), and laser particle size analyzer (Supporting Information, Figure S2b).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Thed iarylethene MOF (1)w as synthesized by using the previously reported method. [23] Ther esulted crystals determined at 293 Ki sc onsistent with the reported value and shown in Figure 1. As UV light cannot penetrate into the crystal samples,t hereby the samples used in this work are treated by ball milling.T he resulted bulk samples are confirmed by powder X-ray diffraction (Supporting Information, Figure S1), SEM (Supporting Information, Figure S2a), and laser particle size analyzer (Supporting Information, Figure S2b).…”
supporting
confidence: 84%
“…[21] Notably,such isomerization usually results in significant difference in optical and electronic properties,leading to an important application as switching material, such as in fluorescent molecular, photochromic chiral, photocontrolled conductivity,a nd liquid-crystal switches. [22] Inspired by this, anchoring diarylethene in MOFs has been recently developed to give aC O 2 adsorption/release switch, [23] energy transfer switch, [24] and singlet oxygen switch in living cells. [25] However, the use of diarylethene to switch gas separation has not been reported.…”
mentioning
confidence: 99%
“…In theseM OFs, changes in pore size are driven by alterations to the conformation of the photoswitchable molecules within the frameworks, which leads to optically induced changes in gas capture.I nt erms of strong controllability of light, the selectivity and regeneration efficiency of this kind of sorbent may be tuned upon specific light irradiation. Most photoresponsive MOFs utilized AZB [54][55][56][57][58][59][60][61][62][63][64] and diarylethene molecules [65][66][67][68] as light-switching units for constructing the frameworks.…”
Section: Lightmentioning
confidence: 99%
“…Guo et al preparedadia-ryletheneM OF (DMOF), namely,Z n(L)-(bpdc)·solvents (bpdc = biphenyl-4,4'-dicarboxylica cid), the Zn II site of which was coordinated with two bpdc 2À oxygen atoms and two diarylethenederived nitrogen atoms. [66] The photoswitchable diarylethene unit can undergo at ransition between open-and closed-ring isomersu nder UV-a nd visible-light irradiation ( Figure 4A). The authors irradiated the single crystal with light and found that it turnedb lue upon UV irradiation and the blue color disappeared upon irradiation with visible light ( Figure 4B).…”
Section: Lightmentioning
confidence: 99%
“…While most of the effort in photo-responsive MOFs has so far been directed towards the study of azobenzene chromophores, it is worth noting that work in this nascent field has also utilised other types of photo-switchable units. 44 42,43 For example, irradiation of a crystal of the material UBMOF-1 with UV-light was found to change the crystal colour into red, indicating a successful ring closure reaction of the diarylethene chromophore.…”
Section: Motions Of Azobenzenes In Periodic Framework Architecturesmentioning
confidence: 99%